“Síndrome de burnout en estudiantes de odontología. Universidad Nacional de Chimborazo, 2019” - María Fernanda, Borja Quicaliquin (2020)
Burnout syndrome considered a work risk factor because it affects both the worker physically and mentally; however, dental students generate this pathology due to the stressors that occur in clinical practice. The objective of this research was to analyze the burnout syndrome in the students of the dental clinics I and IV of UNACH 2019. The methodology that was applied was a descriptive, cross-sectional, mixed-focus, non-experimental approach. The Maslach test and a survey used to determine Burnout syndrome, and the level of satisfaction, an intentional non-probabilistic sample of 72 participants used. It obtained as results that 50% of the respondents presented exhaustion, 73.6% cynicism, and 45.8% under academic performance, as well as in terms of satisfaction level, 23 (31.90%) subjects of clinic IV, and 11 (15.30) o0f the clinic I was dissatisfied. As for the treatments 17 they were exhausted with a medium-high range with the endodontic treatment, 13 had high exhaustion in the treatment of prostheses; 26 presented a high level of cynicism in endodontic, 14 in prostheses and 8 in periodontics; 16 presented a low academic performance in the treatment of endodontic. Therefore, they found significant differences in the exhaustion dimension concerning dental procedures (p= 0.00), and no significant differences were shown in the aspects of cynicism and academic performance (p= 0.394, p=0.659).